General tendencies and priorities in the staff potential development in public libraries of Khabarovsk region and Republic of Belarus: the international cooperation experience - T. A. Romashkina (Библиосфера, 2019)
Sociological research “Human resources of public libraries: modern requirements for professional activity and opportunities for its implementation” was carried out by the Far Eastern State Scientific Library. It was made on the base public libraries in Khabarovsk region within the framework of the partnership and cooperation agreement with the National Library of Belarus. A comparative analysis of the results of the survey of employees in both libraries allowed to identify the characteristic features of personnel problems of public libraries of the Khabarovsk region, to assess the existing the library system of training, to show the level of professional selfassessment of employees, their willingness to accept new knowledge, to determine the professional competence that the managers and ordinary employees of libraries that would like to improve. Despite the geographical remoteness of the Khabarovsk region and Belarus, the peculiarities of social and historical development of the territories, the differences in the structure and density of municipal libraries network, the number of staff, the analysis of the results of the survey of library specialists showed the presence of common personnel problems in the library industry, regardless of the region and its social and economic well-being: the aging of the main staff in libraries, the shortage of specialized human resources and a significant number of specialists in related fields in library industry.